Monitoring (Biodiversity) Aquatic Plants of Iraqi Marshland - Hadeel Radawi Al-Newani (Journal of Global Pharma Technology, 2018)
The study was conducted during December 2014 –December 2015 in ten mainly stations from Iraqi marshlands since been recorded dominated types of aquatic plants in study sites .Results showed that high intensity for aquatic plants  all months was observed at a rate of 73 % Typha sp. , followed Phragmitesaustralis impressive 65%  then Ceratophyllumdermersum 33 % less abundant for being non-indigenous , statistical results highest value to the standard appearance of species Mean±SD (0.999± 0.013 ) (0.480 ± 1). Evaluation of species of aquatic plants in marshes communities response to the change of climate, focusing on the type it , submerged ,emergent and floating and depending on differences and similarities with responses to factor , temperature , O2 , CO2 exposure, level rise water and other expected environmental alterations with natural weather in the region .Advantages environmental climate have an important influence on plant diversity of Iraqi marshes. Based on environmental factors ten ecological regions with the specific plant which is located   climate factors interact to plant influence distribution   and they play an important role in creating ecological biodiversity of Iraq.Keywords: Iraqi marsh, Bio monitoring, Distribution Aquatic plants.